2021
DOI: 10.3389/fmicb.2021.715863
|View full text |Cite
|
Sign up to set email alerts
|

Presence and Germination of the Probiotic Bacillus subtilis DE111® in the Human Small Intestinal Tract: A Randomized, Crossover, Double-Blind, and Placebo-Controlled Study

Abstract: Spore-based probiotics offer important advantages over other probiotics as they can survive the harsh gastric conditions of the stomach and bile salts in the small intestine, ultimately germinating in the digestive tract. A novel clinical trial in 11 ileostomy participants was conducted to directly investigate the presence and germination of the probiotic strain Bacillus subtilis DE111® in the small intestine. Three hours following ingestion of DE111®, B. subtilis spores (6.4 × 104 ± 1.3 × 105 CFU/g effluent d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 34 publications
2
32
0
Order By: Relevance
“…20 Studies have shown Bacillus strains to be capable of germination in the human gut, but the sample size was small and the data is recent. 21 Thus, we sought to employ MPN coatings as ''synthetic spore coats'' on nonsporulated cells to enable their rapid recovery in the GI tract. The importance of a healthy gut microbiome and the negative health effects of an unbalanced microbiome are well known, necessitating improved probiotics for more effective gut implantation.…”
Section: Introductionmentioning
confidence: 99%
“…20 Studies have shown Bacillus strains to be capable of germination in the human gut, but the sample size was small and the data is recent. 21 Thus, we sought to employ MPN coatings as ''synthetic spore coats'' on nonsporulated cells to enable their rapid recovery in the GI tract. The importance of a healthy gut microbiome and the negative health effects of an unbalanced microbiome are well known, necessitating improved probiotics for more effective gut implantation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the B. subtilis strain MB40 has been shown to be safe and support GI health in a randomized, double-blind, placebo-controlled trial of 100 healthy adults [ 17 , 35 ]. Additionally, B. inaquosorum DE111 supplementation has been shown to be safe in both adult and pediatric human subjects [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Altogether, these studies provide a large body of clinical evidence that Bacillaceae spp., including B. subtilis , are safe for human consumption.…”
Section: Introductionmentioning
confidence: 99%
“…At least 6 weeks of daily supplementation with a meal is recommended for clinical trials of spore-forming strains with a primary outcome related to abdominal bloating because consumption with a meal is expected to critically promote growth of the spores and release of bioactive molecules such as antimicrobials and digestive enzymes. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Spores can persist without refrigeration, survive desiccation and heat exposure, and resist the acidic and high bile salt conditions that occur throughout the mammalian GI tract. 16 , 17 Several Bacillaceae strains have been demonstrated to be safe for human consumption. For example, five Bacillus subtilis strains and six Weizmannia coagulans (formerly B. coagulans ) strains are “generally regarded as safe” (GRAS) for use in food without objection from the United States Food and Drug Administration (FDA).…”
Section: Introductionmentioning
confidence: 99%